Correlation between body mass index and body fat distribution with postural stability among female students in UiTM Puncak Alam/ Nurul Shahirah Jamian, Ajau Danis and Zuraini Rosli - Jamian, Nurul Shahirah; Danis, Ajau; Rosli, Zuraini (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Postural stability is an essential component to perform almost every activity in daily living and it may be affected by obesity. The main purposes of this study are to identify the correlation between body mass index (BMI) and body fat distribution with the postural stability and to compare the postural balance performance between the classifications of BMI, and between the types of body fat distributions. A total of 108 female physiotherapy students participated in this study. They were classified into underweight, ideal and overweight & obese groups according to their BMI and into gynoid, uniform, and android groups according to the waist-to-hip ratio (WHR). Postural stability was assessed with three trials of opened and closed eyes single leg stance test (SLST). There was significantly (p< 0.05) negative poor correlation between BMI (r= -0.228) and WHR(r= -0.195) with average score of SLST with vision. The overweight & obese group showed significantly poor postural balance performance with and without vision compare to the ideal group. Thus, being overweight or obese may impair the postural control ability, lead to diminishing in postural stability that may worsen if the individual also has an android type of body fat distributions.